Serum erythropoietin in children with iron deficiency anemia - Çetin, Mualla; Gürgey, Aytemiz; Gümrük, Fatma; Altay, Çiğdem (The Turkish Journal of Pediatrics, 1997)
Serum erythropoietin (EPO) levels were determined in 30 children with iron deficiency anemia. The mean age of the children, hemoglobin (Hb) levels, serum EPO levels and log EPO values were 4.7 ± 5 years, 6.7 ± 1.7 g/dl, 2284 ± 3177 mU/ml and 2.81 ± 0.82 , respectively. In 83 percent of the patients poor diet was the determined cause of iron deficiency and in the remaining 17 percent, chronic blood loss. A significant negative correlation was found between the log EPO values and Hb values ( r = 0.62 , p < 0.01 ). There was no significant correlation between log EPO values and the other parameters [sex, age, mean corpuscular volume (MCV) red blood cell (RBC) red cell distribution width (RDW), serum iron, iron binding capacity]. There was a significant difference in the age of the patients with an Hb value < 5.5 g/dl and those with a value ≥ 5.5 . Significant differences were also observed in log EPO levels among these patients ( p < 0.004 ). The mean Hb value of patients with log EPO values ≥ 3 was lower than that in patients with log EPO values < 3 ( p < 0.003 ). In 20 percent of the patients, serum EPO levels were much lower than the values expected from their Hb level. Serum EPO levels were high in all five patients with a history of chronic blood loss.